Chronology of Glacial Advances and Deglaciation in the Encierro River Valley (29° Lat. S), Southern Atacama Desert, Based on Geomorphological Mapping and Cosmogenic 10Be Exposure Ages - Aguilar, G.; Riquelme, R.; Lohse, P.; Cabré, A.; García, J.-L. (Frontiers in Earth Science, 2022)
The high mountain segments of the valleys of the southernmost Atacama Desert of Chile present Late Quaternary glacial landforms that developed in already incised valleys. Glacier advances and deglaciation have left a geomorphic imprint in the southernmost Atacama Desert. In this work, the glacial landforms of the Encierro River Valley (29.1°S-69.9°W) have been revisited and new detailed geomorphological mapping is provided. This work also includes new 10Be exposure ages from moraine boulders and one age from an ice-molded bedrock surface. The former glacier of El Encierro valley extended 16 km down valley during the last local glacial maximum recorded by a terminal moraine (ENC 1a) whit exposure ages of ~40 ka. Four inboard moraine arcs were deposited upstream in telescopic patterns (ENC 1b-d), whose exposure ages range between ~25 and ~33 ka (ENC 1d). Exposure ages between ~17-24 ka on lateral moraines (ENC 1L) developed during later ice recession of the ENC 1 drift. Thus, the ice mostly disappeared in the main valley before ~18 ka as is also supported by the exposure age obtained from an ice-molded bedrock surface. Seven kilometers up valley from the ENC 1, the ENC 2a-d moraine arcs correspond to small ice advance by ~17-20 ka. The last glacial advance (ENC 2), occurred after deglaciation of the last local glacial maximum (ENC 1), coincides with the start of the Heinrich Stadial Event 1 (HS1; 18-14.5 ka), which is thought to play a direct role in the last glacial termination in the Andes.